Engine noise simulator : creating software for controlling the simulator including a graphical user interface, calibration of the ENS and transfer function measurements - Lundkvist, André (2010)
The purpose of the thesis was to create a graphical user interface (GUI) which can control specific hardware for an engine noise simulator (ENS). The ENS should also be calibrated, and the software should be able to utilise these measurements to control the output sound power level. An ENS is an useful tool to investigate sound transfer paths and to simulate different engines quickly without the need to replace the engine in the cabin. The Scania ENS built at Luleå University of Technology, Luleå, uses 29 loudspeakers with a surface microphone in each individual loudspeaker cavity for calibration purposes. There are loudspeakers on each side of the engine. Software with a Graphical User Interface (GUI) has been written using Matlab’s GUIDE, to create a functional application that is easy to set up and use. The GUI has many options so the user can specify how every loudspeaker should perform. The user can create sound groups, and assign any number of loudspeaker to the group, using individual phase and level settings. The types of sounds can be sinusoidal, noise (both white (Gaussian) and pink), sine sweep (or chirp) and also imported .WAV-files. The GUI also handles all calibration functions, and has functions to verify the condition of the ENS. Programming of the software was done using Matlab, and includes functions to control each loudspeaker individually, create as many different sounds as it’s needed and acquire feedback data from each loudspeaker. The ENS was calibrated by measuring transfer functions between sound power level and volume velocity (source strength) of each loudspeaker element. The volume velocity is calculated from measured pressure inside the loudspeaker cavities. By utilising feedback from the surface microphones located inside each loudspeaker cavity, the user can specify a required sound power level for the output. The calibration was made with the LMS suite. Validerat; 20101217 (root)